Défense Strategy to Support Security, Order, and Resilience in Indonesian Tourism Destination Management - Rachmat Setiawibawa; Dina Subagia (Department of Public Administration, 2026)
Indonesia’s tourism sector faces multidimensional threats that have not been fully integrated into the national defense framework. This study aims to analyze how defense synergy strengthens security, order, and resilience across national tourism destinations. A qualitative descriptive approach is applied through the review of policy documents, defense and security regulations, and case studies in three super priority destinations which are Bali, Mandalika, and Labuan Bajo. Secondary data is drawn from official publications of the Ministry of Defense, the National Disaster Management Agency, the National Cyber and Crypto Agency, and the Ministry of Tourism and Creative Economy, supported by academic literature on tourism resilience and non traditional security. The findings confirm that defense synergy operates through four strategic dimensions. First, threat detection based on intelligence systems that identify potential risks early. Second, protection of vital infrastructure to ensure continuity of tourism activities. Third, readiness and emergency response conducted by the Indonesian National Armed Forces to handle crises effectively. Fourth, international security diplomacy that supports stability and trust in Indonesia as a global tourism destination. The analysis identifies a major structural constraint. Coordination across sectors remains weak. The Indonesian National Armed Forces, the National Police, the National Disaster Management Agency, and tourism authorities operate with limited integration. This condition reduces operational effectiveness and delays response in critical situations. The study concludes that an integrated tourism resilience model provides the most relevant framework. This model aligns defense, security, and tourism governance into a unified system. Implementation of this model will strengthen national resilience, ensure safe tourism operations, and increase global competitiveness. It also supports the long term strategic objective of achieving a secure and resilient Indonesia by 2045.